2021
DOI: 10.3390/ijms23010432
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatibility and Electrical Stimulation of Skeletal and Smooth Muscle Cells Cultured on Piezoelectric Nanogenerators

Abstract: Nanogenerators are interesting for biomedical applications, with a great potential for electrical stimulation of excitable cells. Piezoelectric ZnO nanosheets present unique properties for tissue engineering. In this study, nanogenerator arrays based on ZnO nanosheets are fabricated on transparent coverslips to analyse the biocompatibility and the electromechanical interaction with two types of muscle cells, smooth and skeletal. Both cell types adhere, proliferate and differentiate on the ZnO nanogenerators. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 36 publications
(41 reference statements)
0
5
0
Order By: Relevance
“…Most inorganic piezoelectric materials usually exhibit high piezoelectric properties, such as BaTiO 3 , [64,125] ZnO, [66,[126][127][128] and KNN. [129] However, they often face challenges in practical applications due to issues such as low toughness and poor deformation resistance.…”
Section: Inorganic Piezoelectric Materialsmentioning
confidence: 99%
“…Most inorganic piezoelectric materials usually exhibit high piezoelectric properties, such as BaTiO 3 , [64,125] ZnO, [66,[126][127][128] and KNN. [129] However, they often face challenges in practical applications due to issues such as low toughness and poor deformation resistance.…”
Section: Inorganic Piezoelectric Materialsmentioning
confidence: 99%
“…In recent years, due to its excellent piezoelectric properties, stable chemical properties, abundant yield in Nature and other advantages, researchers from various backgrounds have taken an interest in researching ZnO, which has become a popular material for biomedical sensors and piezoelectric nanogenerators [ 78 ]. The amount of Zn ions released by the nanogenerator does not interfere with cellular activity or trigger an associated inflammatory response, and the nanogenerator itself is biocompatible and does not elicit an inflammatory response [ 30 ].…”
Section: Reviewmentioning
confidence: 99%
“…Blanquer et al . demonstrated that both smooth muscle cells and skeletal muscle cells can adhere, proliferate and migrate on ZnO nanogenerators [ 30 ].…”
Section: Reviewmentioning
confidence: 99%
“…The use of nanogenerators (NG), in the way of piezoelectric nanostructures, for the stimulation of bone and muscle cells has been recently reported. [48,49] The electromechanical NG-cell interaction triggered the opening of ion channels present in the plasma membrane of osteoblast-like cells (Saos-2) and muscle cells inducing intracellular calcium transients, which at the same time is known to regulate muscle contraction. Poly(vinylidene fluoride) (PVDF) has also been explored for bone and neural tissue engineering.…”
Section: Introductionmentioning
confidence: 99%